Business models for sustainable food systems: a typology based on a literature review - Donner, Mechthild; de Vries, Hugo (Frontiers in Sustainable Food Systems, 2023)
The current state of the agri-food system calls for more attention to sustainability. This article explores how diverse business models can contribute to sustainability in food systems, and develops a new business model typology in this domain in which the wider business ecosystem is taken into account. A systematic literature review is done and 37 articles analyzed according to the business model types, their various sustainability dimensions and roles within to the food system. Nine different business model types for sustainable food systems are identified: circular business models, place-based social food networks, new logistics or online food distribution business models, disruptive, sufficiency, inclusive, and family business models, the focal company, and regional food hubs. Collaborative approaches, clear sustainability visions, companies’ values and continuous innovation are important factors for agri-food business models striving for sustainability. More cross-country comparative and cross-disciplinary research is needed for understanding business models and their transitions towards sustainable outcomes within divers and complex food systems.